Performance Evaluation of RESTful Services and AMQP Protocol in Cashless Parking Payment Mobile Apps - Farrabi, Dimas Rizky; Suharjono, Amin; Apriantoro, Roni (Society of Visual Informatics, 2025)
This study explores the challenges surrounding the inefficient use of e-parking applications in Semarang, Indonesia, where issues such as illegal parking and an underperforming digital infrastructure have resulted in lost regional revenue from parking fees. The lack of a robust, user-friendly system has hindered user adoption and limited the application’s effectiveness in managing urban parking. To address these concerns, we developed a modernized e-parking application focused on enhancing usability and system performance. The application design prioritizes intuitive user interaction and seamless integration with existing parking infrastructure. Usability testing using the System Usability Scale (SUS) yielded a score of 80, indicating a high level of user satisfaction and ease of use. In addition, we conducted a comparative analysis of two communication protocols—RESTful and Advanced Message Queuing Protocol (AMQP)—during key application processes, such as vehicle check-in and check-out transactions. Results revealed that AMQP significantly outperformed RESTful in terms of Quality of Service (QoS), particularly with lower response times and minimal packet loss. AMQP consistently met TIPHON standards, achieving a QoS index score of 4, further supporting its suitability for real-time transaction systems in urban environments. This study highlights the critical role of technology optimization in addressing urban mobility issues, reducing illegal parking, and improving public service efficiency. Looking ahead, future development should focus on refining secondary features and introducing new capabilities such as reservation systems, dynamic pricing, and real-time availability tracking to further enhance user engagement and operational effectiveness. The findings emphasize the potential of well-designed e-parking systems to transform urban parking management through smart, scalable technology.